Heterogeneity in the preferential diet of neotropical bats impacts the pancreatic islet mass and α and β cell distribution - Contini, M.; Cruz, G. D.; Althoff, S. F.; Freitas, M. B.; Taboga, S. R. [UNESP]; Rafacho, A. (Elsevier, 2024)
Whether there is a relationship between bats' dietary patterns and evolutionary endocrine pancreas adaptation is not clearly understood. Aiming to contribute to this topic, we evaluated some metabolic and structural parameters in the following adult bats: the frugivorous Artibeus lituratus, the nectarivorous Anoura caudifer, the hematophagous Desmodus rotundus, and the insectivorous Molossus molossus. A. lituratus and A. caudifer diets consist of high amounts of simple carbohydrates, while D. rotundus and M. molossus diets consist of high amounts of proteins or protein and fat, respectively. In our results, A. lituratus and A. caudifer bats exhibited the highest values of relative islet mass (%), islet density (number of islets per pancreas area), and the lowest values of intestinal length among the four species. When adjusted by the body mass (mg/g of body mass), both D. rotundus and A. caudifer bats exhibited the highest islet mass values among the groups. Blood glucose was similar between A. lituratus, D. rotundus, and M. molossus, with the lowest values for the A. caudifer bats. M. molossus bats had the highest plasma cholesterol values among the studied species but exhibited similar plasma triacylglycerol with D. rotundus and A. caudifer bats. β- and α-cell distribution within A. lituratus, A. caudifer, and M. molossus islets achieved an approximate average value of ∼ 66% and ∼ 28%, respectively, a pattern inverted in D. rotundus islets (53% of α cells and 40% of β cells). A. caudifer and D. rotundus exhibited the highest and the lowest β/α-cells ratio per islet, respectively. We conclude that the macronutrient predominance in each bat-eating niche correlates with the morphophysiological pancreas features being the nectarivorous A. caudifer the species with the highest islet mass per body mass and β/α-cells ratio, while the hematophagous D. rotundus showed the highest α-cells apparatus.
Keywords: Chiroptera; Comparative morphology; Endocrine regulation; Food habits; Metabolism